2007
DOI: 10.1523/jneurosci.5648-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Basis of Analgesic Tolerance to Cannabinoids

Abstract: Clinical usage of cannabinoids in chronic pain states is limited by their central side effects and the pharmacodynamic tolerance that sets in after repeated dosage. Analgesic tolerance to cannabinoids in vivo could be caused by agonist-induced downregulation and intracellular trafficking of cannabinoid receptors, but little is known about the molecular mechanisms involved. We show here that the type 1 cannabinoid receptor (CB 1 ) interacts physically with G-protein-associated sorting protein 1 (GASP1), a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
108
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 45 publications
1
108
0
Order By: Relevance
“…This finding, coupled with the result that most striatum/BG nuclei did not exhibit desensitization or were altered only by the highest dose of THC, supports this hypothesis. Regional differences in CB 1 receptor down-regulation could be due to G-protein receptor-associated sorting protein (GASP), which promotes CB 1 receptor down-regulation by augmenting trafficking of the receptor to lysosomes for degradation (Tappe-Theodor et al, 2007). We have shown that CB 1 receptor down-regulation in the hippocampus and striatum is associated with loss of CB 1 protein (Sim-Selley et al, 2006), in agreement with a role for GASP in CB 1 receptor adaptation in the brain.…”
Section: Discussionsupporting
confidence: 66%
“…This finding, coupled with the result that most striatum/BG nuclei did not exhibit desensitization or were altered only by the highest dose of THC, supports this hypothesis. Regional differences in CB 1 receptor down-regulation could be due to G-protein receptor-associated sorting protein (GASP), which promotes CB 1 receptor down-regulation by augmenting trafficking of the receptor to lysosomes for degradation (Tappe-Theodor et al, 2007). We have shown that CB 1 receptor down-regulation in the hippocampus and striatum is associated with loss of CB 1 protein (Sim-Selley et al, 2006), in agreement with a role for GASP in CB 1 receptor adaptation in the brain.…”
Section: Discussionsupporting
confidence: 66%
“…Finally, the receptor is either degraded in lysosomes or it is dephosphorylated (i.e., resensitized) and recycled to the cell membrane. Extensive studies on these processes led to the current concept that receptor internalization and rapid recycling prevent the development of tolerance (for review, see Waldhoer et al, 2004;Tappe-Theodor et al, 2007;Koch and Höllt, 2008;Busch-Dienstfertig and Stein, 2010) (Fig. 1).…”
Section: Intrinsic Induction Of Opioid Peptide Release From Inflammatmentioning
confidence: 99%
“…Accordingly, GPCR internalization is strongly influenced by two of the above mentioned GIPs, the GRKs and arrestins [83]. However, other GIPs can regulate GPCR endocytic trafficking more selectively, for instance GASP which strongly promotes δ-OPR, D 2 R and CB1 trafficking to lysosomes after agonist-induced endocytosis [84][85][86] and SNX1 which binds the PAR1 receptor promoting its post-endocytic trafficking to lysosomes [87]. Overall, it is evident that GIPs play a role in every aspect of GPCR biology: biosynthetic trafficking, anchoring to the site of action, ligand binding, signalling and endocytosis.…”
Section: Modulation Of Gpcr Biology By Gipsmentioning
confidence: 99%